2009
DOI: 10.1364/ol.34.000268
|View full text |Cite
|
Sign up to set email alerts
|

Nonexistence of entanglement sudden death in dephasing of high NOON states

Abstract: We study the dynamics of entanglement in continuous variable quantum systems. Specifically, we study the phenomena of entanglement sudden death (ESD) in general two-mode-N-photon states undergoing pure dephasing. We show that for these circumstances, ESD never occurs. These states are generalizations of the so-called high NOON states (i.e., a superposition of N photons in the first mode, O in the second, with O photons in the first, N in the second), shown to decrease the Rayleigh limit of lambda to lambda/N, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…This number resolution is large enough to realize the global phase estimation for the coherentstate input n ≃ 1. Based upon a Bayesian protocol [19], the achievable phase sensitivity was found almost saturating quantum Cramér-Rao bound over a wide phase interval, in agreement with the theoretical prediction F(ϕ) = F Q = n. To realize higher-precision optical metrology, it requires a bright nonclassical light source with larger mean photon number [15], low photon loss [14,[36][37][38] and low noise [39][40][41][42][43][44][45][46][47][48][49][50], as well as the photon counters with high detection efficiency [51] and large enough number resolution. Q,opt as a function of N res /n for given values of n, using the optimal condition that maximizes Eq.…”
Section: F (Id)supporting
confidence: 64%
“…This number resolution is large enough to realize the global phase estimation for the coherentstate input n ≃ 1. Based upon a Bayesian protocol [19], the achievable phase sensitivity was found almost saturating quantum Cramér-Rao bound over a wide phase interval, in agreement with the theoretical prediction F(ϕ) = F Q = n. To realize higher-precision optical metrology, it requires a bright nonclassical light source with larger mean photon number [15], low photon loss [14,[36][37][38] and low noise [39][40][41][42][43][44][45][46][47][48][49][50], as well as the photon counters with high detection efficiency [51] and large enough number resolution. Q,opt as a function of N res /n for given values of n, using the optimal condition that maximizes Eq.…”
Section: F (Id)supporting
confidence: 64%
“…Moreover sudden birth of entanglement has also been predicted for structured heat baths [55,56] and certain choice of initial conditions of the entangled qubits [57]. In another recent work it has been shown that under a pure dephasing environment for a general two mode N-photon state ESD does not occur [58]. This result was explicitly proven for a general 3-photon state of the form |Ψ = a|30 + b|21 + c|12 + d|03 .…”
Section: Introductionmentioning
confidence: 90%
“…1). Formally, the presence of phase noise can be modeled by the following master equation [17][18][19][20][21][22][23][24][25]:…”
Section: Binary-outcome Detections Under the Phase Diffusionmentioning
confidence: 99%
“…This conclusion is independent of the input states and the presence of noises. Next, we investigate the role of phase diffusion [17][18][19][20][21][22][23][24][25] on the binary-outcome homodyne detection, the parity measurement, and the Z measurement. Our analytical results show that the diffusion plays a role in a form of Nγ, rather than the phase-diffusion rate γ and the mean photon number N alone.…”
Section: Introductionmentioning
confidence: 99%